2007
DOI: 10.1007/s11270-007-9408-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Agricultural Land Use and Management on the Contents of Polycyclic Aromatic Hydrocarbons in Selected Silty Soils

Abstract: The aim of the present study was the influence of various methods of long-term soil utilisation on the content of polycyclic aromatic hydrocarbons (PAH) in selected silty soils. Four soils were selected for the present studies, i.e.: Eutric Fluvisol originating from silty formations, Haplic Phaeozem developed from loess, Haplic Luvisol (non-uniform) developed from silt, Haplic Luvisol developed from loess. Five study sites were chosen, i.e.: apple orchards, hop gardens, fields, grasslands and natural woodland … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
1
6
1
Order By: Relevance
“…The mean concentration of carcinogenic PAHs was 563.1 μg kg −1 (Table 1), and their contributions to Σ16 PAHs were rather uniform, with a median value of 41.7%. The observed fingerprints of Σ16 PAHs are in agreement with other data reported in the literature for agricultural areas (Oleszczuk and Pranagal 2007;Ravindra et al 2008;Duan et al 2015;Suman et al 2016). Polycyclic aromatic hydrocarbons can originate from natural processes such as biomass burning, volcanic eruptions and diagenesis (Pies et al, 2008;Ravindra et al 2008;Akyüz and Çabuk 2010;Katsoyiannis et al 2011;Wang et al 2015).…”
Section: Compositional Profile and Identification Of Pahs Sourcessupporting
confidence: 92%
See 1 more Smart Citation
“…The mean concentration of carcinogenic PAHs was 563.1 μg kg −1 (Table 1), and their contributions to Σ16 PAHs were rather uniform, with a median value of 41.7%. The observed fingerprints of Σ16 PAHs are in agreement with other data reported in the literature for agricultural areas (Oleszczuk and Pranagal 2007;Ravindra et al 2008;Duan et al 2015;Suman et al 2016). Polycyclic aromatic hydrocarbons can originate from natural processes such as biomass burning, volcanic eruptions and diagenesis (Pies et al, 2008;Ravindra et al 2008;Akyüz and Çabuk 2010;Katsoyiannis et al 2011;Wang et al 2015).…”
Section: Compositional Profile and Identification Of Pahs Sourcessupporting
confidence: 92%
“…Generally, the presented results are significantly higher compared to other values reported for the top layer of agricultural soils from non-industrial areas in Poland by Oleszczuk and Pranagal (2007), 105-290 μg kg −1 ; Maliszewska-Kordybach et al (2008,2009), 80-7264 μg kg −1 as well as in Japan, 52.9-2810 μg kg −1 (Chen et al 2017); China, 176.1-563.3 μg kg −1 (Lang et al 2015) and 103.6-5872 μg kg − 1 (Jiao et al 2015) and Norway, 9-11,000 μg kg −1 (Nam et al 2008). Our values even exceed the values of other areas subjected to significant anthropogenic pressure, e.g.…”
Section: Compositional Profile and Identification Of Pahs Sourcescontrasting
confidence: 75%
“…A diagnostic tool that is frequently used for the identification of the sources of PAHs is the MDRs (Oleszczuk and Pranagal 2007 ; Tobiszewski and Namieśnik 2012 ). Their application is based on the assumption that certain PAHs are emitted at relatively constant source-related proportions and that those proportions are retained after reaching the receiver (Katsoyiannis et al 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…Most studies have shown that the principal soil sorption sites for PAH are organic matter (Oleszczuk and Pranagal 2007;Hiller et al 2008). However, some studies pointed out the importance of expansive clays to adsorb hydrophobic organic compounds (HOC) because of their large internal surface area (Hwang et al 2003;Maliszewska-Kordybach 2005).…”
Section: Introductionmentioning
confidence: 99%